2016
DOI: 10.4137/nmi.s29465
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Choline on DNA Methylation and Macronutrient Metabolic Gene Expression in in Vitro Models of Hyperglycemia

Abstract: Choline is an essential nutrient that plays an important role in lipid metabolism and DNA methylation. Studies in rodents suggest that choline may adversely affect glycemic control, yet studies in humans are lacking. Using the human hepatic and placental cells, HepG2 and BeWo, respectively, we examined the interaction between choline and glucose treatments. In HepG2 cells, choline supplementation (1 mM) increased global DNA methylation and DNA methyltransferase expression in both low-glucose (5 mM) and high-gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Third, choline is a major source of methyl group via oxidation to betaine, their important roles in methylation reactions are critical for DNA and histone methylation homeostasis. Jiang et al 17 used the human hepatic HepG2 cell to examine the effect of choline supplementation on DNA methylation, they found that choline supplementation increased both global DNA methylation and DNA methyltransferase expression, suggesting that choline could improve prognosis of HCC. However, in the present study, the favorable associations were only observed between serum choline and HCC survival outcomes, no statistically significant associations between serum betaine and HCC survival outcomes were found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, choline is a major source of methyl group via oxidation to betaine, their important roles in methylation reactions are critical for DNA and histone methylation homeostasis. Jiang et al 17 used the human hepatic HepG2 cell to examine the effect of choline supplementation on DNA methylation, they found that choline supplementation increased both global DNA methylation and DNA methyltransferase expression, suggesting that choline could improve prognosis of HCC. However, in the present study, the favorable associations were only observed between serum choline and HCC survival outcomes, no statistically significant associations between serum betaine and HCC survival outcomes were found.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, choline is a major source of methyl groups via oxidation to betaine, their functions involving the re-methylation of homocysteine to methionine are critical for DNA and histone methylation homeostasis, and therefore have been reported to be associated with cancer risk 2 (including liver cancer) and survival [7][8][9][10] . Experimental studies have reported that when deprived of choline, varying degrees of liver damages and liver diseases developed, including elevated transaminases 11 , affected lipid metabolism and transport 12 , fatty liver 13 , liver cirrhosis 13 and even liver cancer 14 , whereas choline or betaine supplementation ameliorated liver damage 15,16 , and choline supplementation increased global DNA methylation and DNA methyltransferase expression in HepG2 cells 17 , which implied that choline or betaine might not only be associated with hepatocarcinogenesis, but also with liver cancer survival. To date, although scarcely, three case control studies [18][19][20] have evaluated the relationship between choline/betaine and human liver cancer risk, in which consistently favorable effects of choline were found.…”
Section: Introductionmentioning
confidence: 99%
“…Third, choline is a major source of methyl group via oxidation to betaine, their important roles in methylation reactions are critical for DNA and histone methylation homeostasis. Jiang et al [17] used the human hepatic HepG2 cell to examine the effect of choline supplementation on DNA methylation, they found that choline supplementation increased both global DNA methylation and DNA methyltransferase expression, suggesting that choline could improve prognosis of HCC. However, in the present study, the favorable associations were only observed between serum choline and HCC survival outcomes, and no statistically significant associations between serum betaine and HCC survival outcomes were found.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, choline is a major source of methyl groups via oxidation to betaine, their functions involving the re-methylation of homocysteine to methionine are critical for DNA and histone methylation homeostasis, and therefore have been reported to be associated with cancer risk [2] (including liver cancer) and survival [7][8][9][10]. Experimental studies have reported that when deprived of choline, varying degrees of liver damage and liver diseases developed, including elevated transaminases [11], affected lipid metabolism and transport [12], fatty liver [13], liver cirrhosis [13] and even liver cancer [14], whereas choline or betaine supplementation ameliorated liver damage [15,16], and choline supplementation increased global DNA methylation and DNA methyltransferase expression in HepG2 cells [17], which implied that choline or betaine might not only be associated with hepatocarcinogenesis, but also with liver cancer survival. To date, although scarcely, three case control studies [18][19][20] have evaluated the relationship between choline and betaine and human liver cancer risk, in which consistently favorable effects of choline were found.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, there were 4 cell culture conditions during experiments: the normal glucose control group (NG-CO) containing no additional glucose or choline or betaine; the high glucose control group (HG-CO) containing 30 mM additional glucose but no choline or betaine supplement; the high glucose choline supplemented group (HG-CS) containing 30 mM additional glucose and 1 mM choline chloride added to cell culture medium; and the high glucose betaine supplemented group (HG-BS) containing 30 mM additional glucose and 1 mM betaine anhydrous added to cell culture medium. These supplementation levels were selected based on our previous study [ 37 ] to maximize the effect of choline or betaine supplementation on endpoints of interest. Cells were seeded at a starting number of 2 × 10 5 cells per well in 6-well plates in the maintenance medium for 24 h. Thereafter, cells were cultured with one of the four experimental media for 48 h before harvest for RNA extraction.…”
Section: Methodsmentioning
confidence: 99%